2002
DOI: 10.1556/066.2002.31.2.2
|View full text |Cite
|
Sign up to set email alerts
|

On evaluation and comparison of measurement methods with special reference to the meat and meat products

Abstract: The authors discuss the main systematizing principles, not generally used in the field of meat science, regarding critical appreciation and comparison of measurement methods. The presentation of some basic considerations is followed by the discussion of interfering factors. Besides the random error, the role and importance of the constant, proportional and random biases are also treated. The random error is related to the method, while the random bias is related to the test material. A clear distinction is nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Results are presented in Tables 1 and 2. The evaluation of data (KÖRMENDY et al, 1989;KÖRMENDY & ZUKÁL, 2002) showed that the relations presented in Table 1, except sample with serial number 5, can be described with the y ˆ = b.x equation, i.e. proportional relations exist between intensity of P-NMR signal (y) and fat content (x) measured with the Soxhlet method.…”
Section: Resultsmentioning
confidence: 99%
“…Results are presented in Tables 1 and 2. The evaluation of data (KÖRMENDY et al, 1989;KÖRMENDY & ZUKÁL, 2002) showed that the relations presented in Table 1, except sample with serial number 5, can be described with the y ˆ = b.x equation, i.e. proportional relations exist between intensity of P-NMR signal (y) and fat content (x) measured with the Soxhlet method.…”
Section: Resultsmentioning
confidence: 99%